The match - Coben, Harlan, 1962- (Coben, Harlan, 1962- Wilde, 2022)
Harlan Coben returns to Wilde, the man with a past shrouded in mystery who appeared one day in the Ramapo Mountains with no memory of how he got there or the mother and father who abandoned him. Wilde uncovers a major break in the case that may hold the key to revealing the truth of his origins. But the discovery links him with a present-day disappearance and presumed suicide that is much more than at first it appears.